Uji Toksisitas Subkronik Kombinasi Ekstrak Daun Uncaria gambir dan Caesalpinia sappan - Ningsih, Sri; Agustini, Kurnia; Nizar, Nizar; Damayanti, Rini (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Hiperuresemia prevalence tends to increase in society. A combined extract of Uncaria gambir (gambir) and Caesalinia sappan (secang), had been proven to reduce blood uric acid level in vivo. This study aimed to evaluate the subchronic toxicity of this combination in male and female Sprague Dawley rat strain. Animals were randomly grouped into four groups, namely, DOSE-1 (75 mg/kg bw), DOSE-2 (300 mg/kg bw), DOSE-3 (1200 mg/kg bw) and control group gavaged with carrier. The tested sample was given for 7 weeks orally. The result of blood biochemical parameters were not different significantly compared to control (p> 0.05), as well as the results of hematology analysis. However, the NEUT level of female of DOSIS-2 showed lower and significantly different compared to control (p 0,05). Furthermore, this dose did not influence feed intake and body weight of animals in each sex. From this study, it could be concluded that the combination administrated at the dose of 75 mg/kg bw for 7 consecutive weeks did not affect blood biochemistry and hematology and also organ histopathology of kidney, liver, heart, small intestine, and stomach